THE IMPACT OF LEGAL AND EXTRA-LEGAL FACTORS ON SEVERITY OF JUDGES SENTENCING REGARDING NARCOTICS OFFENDERS - Wulandari, Yuli (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
The current study attempts to explain how judge sentencing varies as a response to the legal and extralegal factors of drug offenders. The variables of interest in this research are the recidivism factors among drug offenders. The utilization of ordinary least squares (log-level regression) gives results that mostly coincide with prior studies. However, the empirical evidence found indicates that the roles, gender, religion, and birthplaces of offenders reveal a different fact. This paper acknowledges the limitations related to the data of ethnicity, judge characteristics, and demographic situation in each province. Hence, this model could be improved in future research.